Analisis kebutuhan dan penerapan kurikulum outcome based education pada program studi manajemen pendidikan islam - Jahra, Shofiyah Hafshoh Rabi`ah (Maliki Interdisciplinary Journal, 2026)
The Outcome Based Education (OBE) curriculum emphasizes measurable learning outcomes that align with global demands and the Merdeka Belajar Kampus Merdeka (MBKM) policy. This study aims to analyze the needs and implementation of the OBE curriculum in the Islamic Education Management Study Program through document analysis and literature review. The findings indicate three primary needs: the integration of Islamic values with global competencies, the strengthening of lecturers’ capacity, and adaptation to technological developments. These findings are supported by the thesis mapping conducted in the Islamic Education Management Program at UIN Malang, which shows that curriculum studies require stronger ontological, epistemological, and axiological foundations to guide the implementation of OBE. The application of OBE has been proven to enhance learning efficiency and relevance by producing graduates oriented toward well-defined learning outcomes. This study underscores the necessity of multi-stakeholder collaboration and adaptive study program management to support curriculum revitalization.